High Blood Pressure can be Controlled by Reducing Extra Table Salt Intake - Alamgir, AKM; Ali, Shah Mohammad Keramat; Haque, KMHS Sirajul; Ali, Md. Zulfikar (KYAMC Journal, 2013)
Background: This quasi-experimental community trial was done through door-to-door health education to find out effect of reducing extra table salt intake on patients with high blood pressure. Material and Method: This study was conducted among 4,930 respondents out of 7,474 population (response rate was 65.96%). Respondents had age 18 years or above living in Mohammadpur area of Dhaka city in Bangladesh. Study period was from August 2005 to February 2009. Intervention was for 18 months on 282 (male 69.5% and female 30.5%) respondents with stage-I hypertension. Respondents on trial had no co-morbidity and they were neither aware about their hypertension nor were ever treated for it. The intervention was given person-to-person to quit extra table salt after signing the informed consent form. Follow-up for selected parameters were done after 6, 12 and 18 month of intervention. Data analysis and interpretation were done through SPSS. Result: Mean Blood Pressure of the respondents was found to be 121/78 mmHg. Overall prevalence of hypertension is 20.1% (JNC-7 criteria). After 18m intervention percent reduction of SBP is -7.0% and DBP is -9.9%. Blood pressure of 14.9% (n=42) went up in spite of behavioural risk reduction. Normal blood pressure was found among 7.8% respondents having stage-I hypertension while 17.7% remained at stage-I but their blood pressure is reduced. Multinominal regression analysis showed chi-square value of 25.8 df 13 p=0.018 between use of extra table salt and systolic blood pressure while the value was 28.684 df 11 p= 0.003 for diastolic blood pressure in a -2 Log Likelihood reduced model. At beginning 44% respondents used extra salt while eating. After 6m, 12m and 18m of intervention, extra salt intake was found among 20.6%, 5.0% and 1.8% respondents respectively. Quantitatively extra salt intake reduced from 63±6.5g per week at beginning to 29±4.6g per week after 18m intervention. Change of salt intake was significantly related to change of both SBP (F= 9.688; p=0.000) and DBP (F=6.544; p=0.002). Quality of life was evaluated for both subjective and objective indices. Conclusion: Reversal of hypertension was 56.7% by lifestyle modification and behavioural changes including salt intake reduction. This study confirmed relation of salt with hypertension and also confirmed reduction of blood pressure after reducing salt intake. This study recommended no extra salt intake for patients at risk or with high blood pressure. DOI: http://dx.doi.org/10.3329/kyamcj.v1i2.13314 KYAMC Journal Vol.1(2) January 2011, 48-53